Regional climate variation structures the phyllosphere microbiome of flue-cured tobacco - Zhang, Cheng; Yang, Lei; Zhang, Xiaohua; Zhao, Yuhang; Tang, Jiati; Cheng, Zhijun; Cao, Yi; Wu, Shengjiang; Li, Guanhui; Yang, Long; Wei, Kesu (Frontiers in Plant Science, 2026)
IntroductionClimate change poses major challenges to agriculture, with phyllosphere microbiota playing a key but poorly understood role in plant adaptation.MethodsWe examined structural and functional responses of the phyllosphere microbiome in flue-cured tobacco (Nicotiana tabacum L.) across climatic gradients, using multi-regional sampling, high-throughput sequencing (16S rRNA/ITS), and functional prediction (PICRUSt2).ResultsLeaf starch, total sugar, and reducing sugar contents varied significantly (26.87–32.25%, 14.24–16.74%, and 9.96–11.26%, respectively). Bacterial communities were primarily shaped by precipitation (41.7% variance explained), whereas fungal communities were mainly driven by temperature (27.3%). Microbial networks showed climate-adaptive patterns: complex, cooperative networks (85.99% positive edges) in high-precipitation areas versus simplified, drought-tolerant networks (Nodes: 93, Edges: 1124) dominated by Sphingomonas (86.50%) and Methylobacterium (10.24%) in arid regions. Metabolic potential shifted along the gradient: Communities in low-precipitation areas were enriched with genes potentially encoding starch-degrading enzymes (e.g., α-amylase), while those in high-precipitation areas showed enhanced potential for sucrose synthesis (e.g., via sucrose synthase).DiscussionThis study reveals the adaptive strategies of phyllosphere microbial communities in response to climate variations. Under low-rainfall conditions, community metabolism shifts toward starch degradation, which may aid host osmoregulation. In contrast, under humid conditions, dominant taxa such as Sphingomonas and Methylobacterium collaboratively enhance sucrose synthesis. This metabolic reprogramming aligns with structural changes in microbial networks: transitioning from complex, cooperative networks in humid regions to simplified, stress-tolerant networks in low-rainfall areas. Key metabolic functions are primarily contributed by low-abundance taxa, suggesting the vital role of the rare biosphere in maintaining functional redundancy. Based on these findings, we propose that microbial communities may enhance adaptability by retaining core metabolic functions, such as starch degradation, within rare taxa when facing drought or temperature fluctuations. This study provides a theoretical framework for improving crop climate resilience through microbiome management.